A female infant with an inguinal hernia containing the uterus and bilateral ovaries - Toshiko Takezoe; Kaori Sato; Toshihiko Watanabe; Michinobu Ohno; Masataka Takahashi; Misato Migita; Kenichi Maeda; Yasushi Fuchimoto; Yutaka Kanamori (Elsevier, 2015)
Indirect inguinal hernia is one of the most common congenital abnormality in children. In approximately 15-20% of female patients, the hernia sac contains an ipsilateral ovary, but a few cases have been reported in which the uterus and both ovaries are within the hernia sac. Ultrasonography is a very effective tool to detect prolapsed organs in inguinal hernia; however, detection may be difficult in infants. The present study describes a rare case of inguinal hernia containing the uterus and both ovaries. The hernia was sliding hernia and Bevan's technique was adopted for radical herniorrhaphy. The clinical features of the disease are discussed.